2010
DOI: 10.2135/cropsci2009.09.0538
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Reciprocal Cross Effects of Elite Quality Protein Maize Inbred Lines in Subtropical Environments

Abstract: General combining ability (GCA), specific combining ability (SCA), and reciprocal cross effects information facilitate efficient utilization of inbred lines in a breeding program. A diallel analysis of nine quality protein maize (Zea mays L.) inbred lines was evaluated over seven environments in Zimbabwe. Hybrid × environment interaction was significant for all the traits except for tryptophan content and Quality Index. Thus, phenotyping for tryptophan content and Quality Index can be done using a few environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 17 publications
7
34
2
Order By: Relevance
“…This result is consistent with findings in several studies with QPM germplasm (Pixley and Bjarnason 1993;Vasal et al 1993a, b;Musila et al 2010;Wegary et al 2014). In contrast, studies by Bhatnagar et al (2004) and Machida et al (2010) showed that nonadditive genetic effects were more important than additive genetic effects for control of GY in QPM germplasm. With preponderance of additive gene action for these traits and large genetic variability, a recurrent selection method like half-sib family recurrent selection that emphasizes GCA can be used effectively to improve these traits in this germplasm.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with findings in several studies with QPM germplasm (Pixley and Bjarnason 1993;Vasal et al 1993a, b;Musila et al 2010;Wegary et al 2014). In contrast, studies by Bhatnagar et al (2004) and Machida et al (2010) showed that nonadditive genetic effects were more important than additive genetic effects for control of GY in QPM germplasm. With preponderance of additive gene action for these traits and large genetic variability, a recurrent selection method like half-sib family recurrent selection that emphasizes GCA can be used effectively to improve these traits in this germplasm.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the mean protein content (12.8/100 g) of the biofortified maize varieties of this study was much higher than the documented values for white maize (Machida et al, 2010;Johnson, 2000). The finding that the provitamin A-biofortified maize varieties had a higher protein and fat content relative to the white maize is encouraging.…”
Section: Resultscontrasting
confidence: 78%
“…Bhatnagar et al (2004) and Machida et al (2010) reported that nonadditive gene effects were more important than additive gene effects for GY, while additive genes were common in affecting PH, AD, and SD. These crosses consisted of at least one parent with a high GCA effect and increased concentration of favorable alleles for GY.…”
Section: Discussionmentioning
confidence: 99%